SINERGI KURIKULUM MERDEKA DAN KURIKULUM 2013: Peluang dan Tantangan Guru di SDN Tanah Merah - Fauzan Naufal Ibrahim; Reza Al Farabi; Miftachudin; Meliza Rika Safitri (Education and Community Service Journal (EduServe), 2025)
Education will always be related to the curriculum. Without a curriculum it will not be possible for education to run well effectively and efficiently as desired. Every curriculum change in the education unit has a strong basis. Curriculum changes cannot be separated from the times that are currently all digital. The collaboration of these two approaches has the aim of optimizing the potential of students and preparing them to face challenges in the age of globalization. This research uses qualitative research methods through observation, interviews, and documentation at SDN Tanah Merah 01, East Sepatan District, Tangerang Regency. the synergy of these two curricula also presents various opportunities. Educators can develop creativity in designing learning that is more contextual and in accordance with the needs of students. A more flexible approach in the Merdeka Curriculum provides an opportunity for educators to vary without being too bound by a monotonous curriculum structure. In addition, strengthening collaboration between educators and improving skills through training and discussions are added values that support the successful implementation of this synergy. Through the synergy approach of the two curricula, SDN Tanah Merah 01 is committed to creating a more adaptive, innovative and inclusive learning environment.